Salvianolic Acid A Suppresses DNCB-Induced Atopic Dermatitis-Like Symptoms in BALB/c Mice. (14th October 2021) - Jeon, Wi-Jin; Lee, Ju-Hyun; Lee, Jung-Eun; Son, So-Eun; Okajima, Fumikazu; Chung, Ki Wung; Im, Dong-Soon
Abstract : Prevalence of atopic dermatitis (AD), a chronic, pruritic, and relapsing inflammatory skin disorder, is growing. Because available therapeutics is limited, immune regulators from natural resources could be helpful for treating AD symptoms. The root of Salvia miltiorrhiza Bunge (Lamiaceae) has been studied for the treatment of inflammatory diseases, including dermatologic disorders in Korea. This study examined the effect of salvianolic acid A on AD-like symptoms. Sensitization on the dorsal skin and repeated application on the ears with 2, 4-dinitrochlorobenzene (DNCB) were performed in BALB/c mice to induce AD-like skin lesions. After induction of atopic dermatitis, salvianolic acid A (5 and 10 mg/kg) or dexamethasone (10 mg/kg) were administrated via intraperitoneal injection for 3 weeks. Salvianolic acid A suppressed DNCB-induced AD-like symptoms like ear skin hypertrophy and decreased mast cell infiltration into skin lesions. Salvianolic acid A not only reduced DNCB-induced increase of serum IgE but also lowered levels of the Th2 cytokines (IL-4 and IL-13), Th1 cytokine (interferon- γ ), and Th17 cytokine (IL-17A). Furthermore, salvianolic acid A blocked DNCB-induced lymph node enlargement. In summary, these results suggest that salvianolic acid A might have a therapeutic potential for the treatment of AD.